Insight into regulation of adventitious root formation by arbuscular mycorrhizal fungus and exogenous auxin in tea plant (Camellia sinensis L.) cuttings - Chen, Weili; Shan, Wenshu; Niu, Tingting; Ye, Tao; Sun, Qinyu; Zhang, Jiaxia (Frontiers in Plant Science, 2023)
Adventitious root (AR) development, affected by various biotic and abiotic factors, is the most important procedure in tea plant (Camellia sinensis L.) cutting propagation.Establishing symbiotic relationships with most terrestrial plants, AMF (Arbuscular mycorrhizal fungus) can mediate the AR formation of several herbaceous and woody plants in previous studies. In this paper, effects of combined application of AMF and exogenous auxin on AR formation of cuttings from different tea plant varieties ('Pingyangtezao', 'Longjing 43' and 'Longjingchangye') were studied. Then we also performed RNA-Seq analysis with 'Pingyangtezao' cuttings aiming to find the possible auxin-related pathway of AM fungal regulation on AR formation. To accurately uncover the regulatory mechanism of AMF on AR formation of tea cuttings, rooting process were separated into four stages (S0, non-rooting; S1, AR protrusion; S2, AR formation and S3, AR elongation) at the same sampling time. Results showed that IBA treatment increased the mycorrhizal colonization rate, especially in 'Pingyangtezao' variety (from 37.58% to 46.29%). Both inoculating AMF and addition of IBA promoted the AR formation, and rooting of different tea plant varieties showed different dependence on auxin. AMF could alleviate the effect of auxin-related inhibitors (2,3,5triiodobenzoic acid, L-α-(Aminooxy)-β-phenylpropionic acid and α-(phenylethyl-2oxo)-IAA) on rooting of tea cuttings, even though the colonization of AMF was hindered at various degrees. Transcriptomic analysis showed that different numbers of differentially expressed genes (DEGs) at various rooting stages of tea cuttings with the most at S2 stage (1360 DEGs), indicating the increasing regulation by AMF with the development of AR. Similar trend was found in auxin-related DEGs, and family genes of YUC, GH, PIN, LAX, SAUR, AUX, and ABP involved in the AM fungal regulation on AR formation of tea cuttings. Additionally, AMF strongly mediated auxin transport and signal transduction pathways in tea cuttings as showed by the results of correlation analysis. Overall, interaction of AMF and exogenous auxin in promoting rooting and the preliminary mechanism of AMF regulating AR formation of tea cuttings was deciphered in this paper, which may provide a basis for further deep mechanistic research and cutting propagation of tea production.